2019
DOI: 10.1111/1556-4029.14113
|View full text |Cite
|
Sign up to set email alerts
|

microRNA Detection in Blood, Urine, Semen, and Saliva Stains After Compromising Treatments

Abstract: Evaluation of microRNA (miRNA) expression as a potential method for forensic body fluid identification has been the subject of investigation over the past several years. Because of their size and encapsulation within proteins and lipids, miRNAs are inherently less susceptible to degradation than other RNAs. In this work, blood, urine, semen, and saliva were exposed to environmental and chemical conditions mimicking sample compromise at the crime scene. For many treated samples, including 100% of blood samples,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…Circulating miRNAs are promising biomarkers, highly stable at extreme conditions of pH, chemical treatments and temperature. Moreover, circulating miRNAs are preserved from RNAse activity because they are carried by RNA-binding proteins in extracellular vesicles and lipoprotein [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Circulating miRNAs are promising biomarkers, highly stable at extreme conditions of pH, chemical treatments and temperature. Moreover, circulating miRNAs are preserved from RNAse activity because they are carried by RNA-binding proteins in extracellular vesicles and lipoprotein [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, microRNAs (miRNAs) are gaining increasing attention in the field of neuropsychiatric diseases, given the important regulatory roles of miRNAs in cell growth, neural differentiation, and synaptic plasticity. 19 Additionally, miRNAs are suitable for biomarkers because they are abundant in various body fluids (such as blood, saliva, and urine), 5 and these body fluids can be collected easily and non-invasively. In fact, a number of studies have shown blood miRNA aberrations in patients with MMD when compared with healthy control (HC) subjects, and several blood miRNAs have been proposed as potential biomarkers for the diagnosis of MDD.…”
Section: Introductionmentioning
confidence: 99%
“…The application of circulating RNA molecules, including non-coding RNAs (ncRNAs), as biomarkers has been widely explored in the last few decades; miRNAs have been suggested as diagnostic biomarkers for several diseases, including neurodegenerative [ 8 , 9 ], neurodevelopmental [ 10 ], traumatic [ 11 ], neoplastic [ 12 , 13 ], and metabolic conditions [ 14 , 15 ]. Indeed, miRNAs have been detected in all analyzed biological fluids [ 16 , 17 , 18 ], making them useful as disease biomarkers measurable in all body districts. Similarly, long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs), a recently discovered class of ncRNAs, are emerging as new potential disease biomarkers, also in AD [ 19 ].…”
Section: Introductionmentioning
confidence: 99%